The Role Of Gendered Livelihoods In Shaping Cattle Management In Smallholder Farming Households In Nusa Tenggara Barat - Baiq Yulfia Elsadewi Yanuartati; Janet Reid; David Gray (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
This study explored how gender roles influenced the management of cattle farming in smallholder households in Nusa Tenggara Barat (NTB), Indonesia. In this setting, cattle were not only a key source of income but also held cultural value. However, traditional social norms still tended to limit women’s involvement in cattle-related activities. Guided by Livelihoods Theory, this research examined how gendered roles shaped labor roles, access to resources, and decision-making within household cattle management. Using a qualitative case study approach, the study drew on semi-structured interviews with 25 men and women from cattle-farming households in NTB. The data were analyzed thematically to identify patterns in gender roles, control over resources, and access to support systems, which shaped decisions on cattle. The findings suggested that patriarchal norms continued to restrict women’s access to productive assets, limiting their participation in cattle management. While cattle served as a form of household savings, women often relied on them for investment, especially when they lacked access to credit due to limited ownership of collateral. Meanwhile, men were often seen as more mobile and capable of managing cattle, particularly bulls, while women were more involved with small livestock such as poultry and goats. Women were also commonly excluded from livestock farmer groups, which served as key gateways to government livestock support and grants. This exclusion reinforced gender gaps in cattle ownership, economic opportunities, and access to public agricultural resources. The study highlighted the need for more inclusive approaches to support women’s roles in cattle farming and rural livelihoods.